Science communication for the press: hybrid model of Agência Bori texts based on five essential questions (Intercom - Brazilian Journal of Communication Sciences, 2022)
Nine out of ten Brazilians cannot name an institution that does research in the country or a Brazilian scientist (CGEE, 2019) – which reveals the need for strategies to connect the press and science in Brazil. Agência Bori is part of this field, an initiative that disseminates Brazilian scientific studies to journalists across the country and explains them through a hybrid text, which is placed between a press release and a news text. In this article, we present the construction of the Agência Bori hybrid model of science communication text based on five essential questions: What is the main finding of the research? How was the search done? How do the results change people’s lives? How do the results change what was already known in the area of knowledge? What happens now in the face of the results/conclusions? Preliminary experiences of monitoring the repercussion of studies disseminated to the press show that the model is well accepted in the journalistic environment.
Keywords: Science journalism; Science communication; Textual model; Journalism; Public understanding of science